CLINICAL AND PROGNOSTIC ASPECTS OF THE ASSESSMENT OF BRAIN NATRIURETIC PEPTIDE AND GRACE IN PATIENTS WITH ACUTE CORONARY SYNDROME - Kopitsa, N. P.; Degtyarevа, O. V.; Petynina, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
One of the achievements of recent years in the field of cardiology is to create a model for risk assessment of patients with acute coronary syndrome (ACS), which allows you to select the most optimal treatment strategy. In clinical practice used models for calculating risk TIMI, GRACE, PURSUIT, based on clinical data, ECG, assessment of biochemical markers. In order to improve forecast accuracy in our study, we used the most popular scale of GRACE in conjunction with indicators of the N-terminal region prohormone brain natriuretic peptide (NT-proBNP) in 126 patients with ACS for short-and long-term prognosis. We found that the highest level of cardiac mortality was observed in patients with indicators GRACE> 4 and at the level of NT-proBNP> 1271 pg / ml.